1988
DOI: 10.1182/blood.v71.3.728.728
|View full text |Cite
|
Sign up to set email alerts
|

A role for thrombomodulin in the pathogenesis of thrombin-induced thromboembolism in mice

Abstract: The antithrombotic action of thrombomodulin was studied in mice. Rat and mouse thrombomodulin were isolated from lung acetone powders, and anti-rat thrombomodulin antibodies were prepared in rabbits. The antibodies neutralized both mouse (Kd approximately 150 nM) and rat thrombomodulin (Kd approximately 50 nM). A role for thrombomodulin in vivo was shown in mice injected intravenously (IV) with thrombin. All mice injected with 15 U thrombin (bolus) died of thromboembolism (mean survival 55 minutes), whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…However, administration of hTBM attenuates the consequences of thrombin‐induced thromboembolism in mice and rats . Thrombomodulin has been shown to be involved in the regulation of coagulation, complement, and anti‐inflammation and cell proliferation, which have a protective role against microvascular thrombosis . Furthermore, our results presented earlier also suggest that hTBM expression in the donor organ along with anti‐CD40 mAb treatment may help to prolong the xenograft survival …”
Section: Discussionsupporting
confidence: 62%
“…However, administration of hTBM attenuates the consequences of thrombin‐induced thromboembolism in mice and rats . Thrombomodulin has been shown to be involved in the regulation of coagulation, complement, and anti‐inflammation and cell proliferation, which have a protective role against microvascular thrombosis . Furthermore, our results presented earlier also suggest that hTBM expression in the donor organ along with anti‐CD40 mAb treatment may help to prolong the xenograft survival …”
Section: Discussionsupporting
confidence: 62%
“…As the plasma or serum levels of HMGB1 in DIC or septic patients have been reported to range from 0 to 10 n m [7,16,17], the percentage inhibition of APC generation in such patients may be about 10%. Considering that 40% inhibition of APC generation or heterozygous deletion of TM was previously reported to cause thrombosis in animal models [29,30], HMGB1 in septic patients at a concentration of about 1 n m may not be sufficient to cause thrombosis through inhibition of APC generation alone. It is therefore possible that other mechanisms, such as increased tissue factor expression, are also important in the aggravation of DIC by HMGB1.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative approach, several studies have documented that various forms of solubilized TM are capable of activating protein C in vivo . For example, Kumada et al (36) observed that TM prolonged the survival of mice in a model of thrombin‐induced thromboembolism. Other studies have demonstrated that administration of TM reduces endotoxin induced lung injury (37,38) and thrombosis from disseminated intravascular coagulation (DIC) in rats and monkeys (39–41), limits thrombosis in an arteriovenous shunt model in rats (42), attenuates thrombotic glomerulonephritis in rats (43) and decreases trauma induced spinal cord injury (44).…”
Section: Discussionmentioning
confidence: 99%